ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS UNTUK PERENCANAAN DAN PENGENDALIAN KEUANGAN PADA RUMAH SAKIT MITRA SEJATI - Reza Ary Pratama Reza; Alistraja Dison Silalahi; Dwi Saraswati (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2021)
Abstract The objective of this research was to analyze the accounting information system for cash receipts and disbursements for financial planning and control at Mitra Sejati Hospital Medan. The problem raised in this research is that the accounting information system at Mitra Sejati Hospital has not been effective, and there are still improvements in the system. The object of this research is Mira Sejati Hospital. This research is a qualitative research and uses descriptive analysis with a flowchart approach. Methods of data analysis by collecting, analyzing data in the application of accounting information systems in Mitra Sejati hospital. The results of the research indicate that a good accounting information system has played a role in improving the internal control system for cash receipts. This can be seen from the cash receipts accounting information system whose system is online in collaboration with third parties. So that the accounting information system can guarantee cash security implemented by Mitra Sejati Hospital so that it plays an important role in improving the internal control system in terms of providing and providing accurate and reliable information on cash receipts.